The Social Environment and Neurogenesis in the Adult Mammalian Brain - Lieberwirth, Claudia; Wang, Zuoxin (Frontiers in Human Neuroscience, 2012)
Adult neurogenesis—the formation of new neurons in adulthood—has been shown to be modulated by a variety of endogenous (e.g., trophic factors, neurotransmitters, and hormones) as well as exogenous (e.g., physical activity and environmental complexity) factors. Research on exogenous regulators of adult neurogenesis has focused primarily on the non-social environment. Most recently, however, evidence has emerged suggesting that the social environment can also affect adult neurogenesis. The present review details the effects of adult-adult (e.g., mating, conspecific, and chemosensory signal exposure) and adult-offspring (e.g., gestation, parenthood, and exposure to offspring) interactions on adult neurogenesis. In addition, the effects of a stressful social environment (e.g., lack of social support and dominant-subordinate interactions) on adult neurogenesis are reviewed. The underlying hormonal mechanisms and potential functional significance of adult-generated neurons in mediating social behaviors are also discussed.